2019
DOI: 10.1111/asj.13212
|View full text |Cite
|
Sign up to set email alerts
|

Functional efficacy analysis ofAngelica gigasNakai on chicken myoblast cells through cell‐based in vitro assay

Abstract: The value‐added products in livestock industry is one of the key issues in order to maximize the revenue and to create a new business model. Numerous studies have suggested application of herbal plants as feed additives to increase health, productivity, and/or high‐quality product in livestock. In this study, the first experiment was designed to develop in vitro evaluation system by using primary chicken myoblast (pCM) cells isolated from pectoralis major of 10‐day‐old male embryos. Subsequently, to evaluate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Additionally, Zhou et al (2015) and Niu et al (2019) reported that dietary supplementation of broilers with fermented Ginkgo biloba rations and fermented Ginkgo biloba leaves resulted in significant decreases in serum levels of triglycerides and cholesterol. Lee et al (2019) reported that AGN as a lipolytic supplement showed the down-regulation of proliferation and differentiation in chicken myoblast cells, and affected the metabolic pathways of glycolysis and fatty acids by suppressing fat accumulation followed by amelioration of hepatic steatosis and hyperlipidemia and activating glycolysis.…”
Section: Biochemical Indicatorsmentioning
confidence: 99%
“…Additionally, Zhou et al (2015) and Niu et al (2019) reported that dietary supplementation of broilers with fermented Ginkgo biloba rations and fermented Ginkgo biloba leaves resulted in significant decreases in serum levels of triglycerides and cholesterol. Lee et al (2019) reported that AGN as a lipolytic supplement showed the down-regulation of proliferation and differentiation in chicken myoblast cells, and affected the metabolic pathways of glycolysis and fatty acids by suppressing fat accumulation followed by amelioration of hepatic steatosis and hyperlipidemia and activating glycolysis.…”
Section: Biochemical Indicatorsmentioning
confidence: 99%